Administrasi Keimigrasian dalam Perspektif Good Governance: Studi Literatur Tentang Transparansi dan Akuntabilitas Pelayanan Keimigrasian - Rafii’ Abdurrochman; Arief Febrianto; Wisnu Widayat (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the implementation of good governance principles in Indonesia’s immigration administration, focusing on transparency and accountability aspects. It employs a descriptive qualitative approach through a literature review of scholarly articles, policy reports, and relevant regulations. The establishment of the Ministry of Immigration and Corrections (Kemenimipas) under Presidential Regulation No. 157 of 2024 marks a significant milestone in the institutional reform of immigration services in Indonesia. The findings reveal that transparency is implemented through digitalized services such as M-Paspor and e-Visa, along with public access to information. Meanwhile, accountability is reflected in performance reporting, public complaint systems, and external oversight by institutions such as the Ombudsman. However, a gap remains between theoretical ideals and practical implementation, particularly regarding human resource capacity, technological access, and policy consistency across regions. This study concludes that transparency and accountability are not merely administrative requirements but essential foundations for building high-quality, responsive, and trustworthy immigration services. The study recommends regulatory updates, stronger performance evaluations, and investments in human resources and digital infrastructure.